Network study of the nutritional patterns, the metabolic and the psychological status among overweight-obese young adults - Reivan Ortiz, Geovany Genaro; Granero, Roser; Icaza, Daniel; Maraver-Capdevila, Laura (Frontiers in Nutrition, 2025)
BackgroundThe classification of severely overweight individuals as “metabolically unhealthy obese” (MUO) versus “metabolically healthy obese” (MHO) is based on the presence or absence of cardio-metabolic risk factors, respectively. However, evidence is limited for the differences in the underlying relationships between nutritional habits, physical measures and psychological features. This study applies network analysis to visualize the interrelationships between nutritional dietary patterns, physical measures and psychological variables in young overweight or obese adults. In addition, we identified the nodes with the highest centrality indexes, and explored their empirical modularity. Stratified networks were obtained separately for MHO versus MUO subsamples, in order to explore differences in metabolic status.MethodsData were collected from N = 188 young overweight or obese adults (university students, men and women aged 18 and 25 years) and subsequently analyzed.ResultsIn the MHO group, stress was identified as the bridge node, with the strongest connections with other psychological features (depression and anxiety), physical measures (body mass index, triacylglycerol, hypertension and glucose) and a nutritional pattern characterized by the intake of carbohydrates, fat and sodium. In contrast, in the MUO group, a nutritional pattern characterized by high consumption of fats and sodium, closely followed by cholesterol levels, emerged as the bridge node, with strong links to other dietary habits and variables.ConclusionIdentification of the most influential nodes among young individuals with and without cardio-metabolic risk factors provides valuable insights for the design of targeted treatment strategies. A combination of classical approaches (such as change in diet, physical activity, anti-obesity drugs and bariatric surgery) with psychotherapy (such as cognitive behavioral strategies, particularly stress management and problem-solving techniques) is especially important among MHO patients.